2021
DOI: 10.1186/s41256-021-00204-4
|View full text |Cite
|
Sign up to set email alerts
|

Does city lockdown prevent the spread of COVID-19? New evidence from the synthetic control method

Abstract: Background At 10 a.m. on January 23, 2020 Wuhan, China imposed a 76-day travel lockdown on its 11 million residents in order to stop the spread of COVID-19. This lockdown represented the largest quarantine in the history of public health and provides us with an opportunity to critically examine the relationship between a city lockdown on human mobility and controlling the spread of a viral epidemic, in this case COVID-19. This study aims to assess the causal impact of the Wuhan lockdown on popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The results show that tourism and catering industry are influenced more greatly than audio-visual and digital entertainment, and the service functions and the development of facilities should be improved. Yang explored the causal relationship between the incidence of COVID-19 disease and the incidence of new COVID-19 cases in Wuhan of China using panel data from 279 cities [24]. The result shows that lockdown can be an effective short-term tool to contain and slow the spread of the virus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results show that tourism and catering industry are influenced more greatly than audio-visual and digital entertainment, and the service functions and the development of facilities should be improved. Yang explored the causal relationship between the incidence of COVID-19 disease and the incidence of new COVID-19 cases in Wuhan of China using panel data from 279 cities [24]. The result shows that lockdown can be an effective short-term tool to contain and slow the spread of the virus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yang (2021) analyzed that when the situation comes with no effective vaccination, city-wide locking down can positively reduce population movement and significantly contain and delay the spread of Covid-19 in the short term [6]. And the authors also concluded that the unprecedented citywide quarantine in human history in Wuhan provided valuable time for the world to prepare for the fight against the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors quoted the analysis of Athey and Imbens to evaluate this method, "SCM method is arguably the most important innovation in the policy evaluation literature in the last 15 years. [6]". After the detailed modeling and controlling the bias, the authors showed a fluctuating decreasing downward trend at the point of Wuhan locking down.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, because of the fear of community spread, people could not travel to hospitals to seek the necessary support. Due to the coronavirus, countries issued lockdown and travel bans [2][3][4][5] to prevent the spread.…”
Section: Introductionmentioning
confidence: 99%